2015
DOI: 10.1186/s11671-015-1205-8
|View full text |Cite
|
Sign up to set email alerts
|

Self-Shadowing Deposited Pure Metal Nanohelix Arrays and SERS Application

Abstract: In this work, one-step glancing angle deposition is utilized to fabricate gold and silver nanohelix arrays (NHAs) on smooth glass substrates. During deposition, the substrate is cooled using liquid nitrogen and rotated with a tunable spin rate. The substrate spin rate is tuned to match the deposition rate to yield a spiral-like helix structure. The morphologies and optical properties of spiral-like Ag and Au NHAs are measured and compared. The polarization-dependent reflectance of Au NHA leads to a strong g-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…However, expensive lithography is required to pattern the seeded surface of the substrate [7]. Recent work has revealed that pure metal helix arrays can be obliquely deposited on smooth substrates via self-shadowing [8][9][10][11]. Rather than using liquid nitrogen to cool the substrate to a temperature of around −140 • C, metal helix arrays can be grown on a substrate at a temperature of 10 • C using ice water for substrate cooling, as has been proposed in recent works [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, expensive lithography is required to pattern the seeded surface of the substrate [7]. Recent work has revealed that pure metal helix arrays can be obliquely deposited on smooth substrates via self-shadowing [8][9][10][11]. Rather than using liquid nitrogen to cool the substrate to a temperature of around −140 • C, metal helix arrays can be grown on a substrate at a temperature of 10 • C using ice water for substrate cooling, as has been proposed in recent works [12].…”
Section: Introductionmentioning
confidence: 99%
“…There have yet to be temperature-SERS studies done with other substrates, such as polymers, that have significantly different thermal conductivities to typical silicon/glass substrates. While changes in geometries were observed as a temperature dependence during oblique angle depositions, there is little in literature that studies this temperature dependence with other nanostructures [15,53], perhaps this will be a new area that will be expanded in the near future.…”
Section: Temperature Dependent Oblique Angle Depositionmentioning
confidence: 99%
“…Substrate rotation during OAD can generate helical structures, Jen et al have investigated nanohelix arrays using oblique angle depositions at −140 • C that were applied to SERS investigations. In their 2015 work, they compared nanohelix arrays made from Ag and Au, where it was found that gold was the better SERS material for this configuration [53]. This study compared the SERS spectra of BPE using nanohelix and nanorod arrays made with Ag, Figure 10 is from [53], indicating clearer SERS spectrum with a nanohelix array.…”
Section: Geometries Of Oad Derived Sers Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…A metal nanohelix array can reportedly be obliquely deposited on a seeded substrate by spinning the cooled substrate during deposition32. Our recent work has shown that silver and gold nanohelix arrays can be obliquely deposited on a smooth substrate at with an optimal spin rate with respect to the deposition rate3334. Without patterned substrates, nanohelices are grown by self-shadowing; the nanohelices are distributed densely, and rod-to-rod gaps with widths of less than 10 nm are randomly and densely distributed within the array.…”
mentioning
confidence: 99%